2020
DOI: 10.3390/ijerph17103707
|View full text |Cite
|
Sign up to set email alerts
|

Green Microalgae Scenedesmus Obliquus Utilization for the Adsorptive Removal of Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) from Water Samples

Abstract: In view of the valorisation of the green microalga Scenedesmus obliquus biomass, it was used for the biosorption of two nonsteroidal anti-inflammatory drugs, namely salicylic acid and ibuprofen, from water. Microalgae biomass was characterized, namely by the determination of the point of zero charge (pHPZC), by Fourier transform infrared (FT-IR) analysis, simultaneous thermal analysis (STA) and scanning electron microscopy with energy dispersive spectroscopy (SEM/EDS). Kinetic and equilibrium batch experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 84 publications
0
11
0
2
Order By: Relevance
“…The broad peak at 3440 1/cm corresponds to the presence of -OH groups, the peaks at 2925 and 2958 1/cm correspond to the stretching of the C-H bonds, the peaks from 1395–1460 1/cm corresponds to the bending vibration of CH 2 and CH 3 groups, and symmetrical stretching of the C=O group in the formation of carboxyl (-COOH). The peak around 1253 1/cm corresponds to organic phosphates [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The broad peak at 3440 1/cm corresponds to the presence of -OH groups, the peaks at 2925 and 2958 1/cm correspond to the stretching of the C-H bonds, the peaks from 1395–1460 1/cm corresponds to the bending vibration of CH 2 and CH 3 groups, and symmetrical stretching of the C=O group in the formation of carboxyl (-COOH). The peak around 1253 1/cm corresponds to organic phosphates [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the removal capacity that some of these sorbents have is far from that achieved with commercial sorbents such as activated carbon. Although the comparison data are scarce, the values obtained indicate the need to search for biomaterials with greater capacity-for example, the biomass of Scenedesmus obliquus had a maximum removal capacity of salicylic acid and ibuprofen of 63 and 11.9 mg/g, respectively; instead in the same conditions, activated carbon had 250 and 147 mg/g [144].…”
Section: Other Organic Pollutantsmentioning
confidence: 99%
“…FTIR analysis contributes to the explanation of biosorption mechanism through the description of their functional group. The presence of secondary amines -NH and primary amines -NH 2 in RB, and AC clarified the ability of algal biosorbent to form the positive cations performing ionic pond with AR1 ions (Tan et al 2018;Déniel et al 2020;Silva et al 2020). The stretching ponds in the -CH group and aliphatic -CH 2 group have a central role in the adsorption process as they possess a high ability to form free radicals that attract the AR1 ions (Asemani et al 2020).…”
Section: Characteristics Of De-oiled Biosorbentmentioning
confidence: 94%
“…3 illustrates the functional groups of RB, AC, and AB. The presence of weak secondary amines -NH and primary amines -NH 2 is proved by the peaks ranging from 3758.58 to 3830.9 cm −1 (Tan et al 2018;Déniel et al 2020;Silva et al 2020). The border absorption peaks at wavelength 3156.90-3275.50 cm −1 Removal% =111.1621 − 0.45771D − 5.38829P + 0.075686T + 0.39671P 2 elucidate the existence of stretching hydroxyl group -OH (Kumar et al 2019) that found in all samples with a higher-intensity value for biosorbent RB.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 98%